Hypermethylation of Smad7 in CD4+ T cells is associated with the disease activity of rheumatoid arthritis - Hu, Yiping; Xu, Bihua; He, Juan; Shan, Hongying; Zhou, Gengmin; Wang, Deli; Bai, Lu; Shang, Hongxi; Nie, Liping; Pan, Fan; Lan, Hui Yao; Wang, Qingwen (Frontiers in Immunology, 2023)
Background: Smad7 is protective in a mouse model of rheumatoid arthritis. Here we investigated whether Smad7-expressing CD4+ T cells and the methylation of Smad7 gene in CD4+ T cells contribute to the disease activities of RA in patients. Methods: Peripheral CD4+ T cells were collected from 35 healthy controls and 57 RA patients. Smad7 expression by CD4+ T cells were determined and correlated with the clinical parameters of RA including RA score and serum levels of IL-6, CRP, ESR, DAS28-CRP, DAS28-ESR, Swollen joints and tender joints. Bisulfite sequencing (BSP-seq) was used to determine the DNA methylation in Smad7 promoter (-1000 to +2000) region in CD4+ T cells. In addition, a DNA methylation inhibitor, 5-Azacytidine (5-AzaC), was added to CD4+ T cells to examine the possible role of Smad7 methylation in CD4+ T cell differentiation and functional activities. Results: Compared to the heath controls, Smad7 expression was significantly decreased in CD4+ T cells from RA patients and inversely correlated with the RA activity score and serum levels of IL-6 and CRP. Importantly, loss of Smad7 in CD4+ T cell was associated with the alteration of Th17/Treg balance by increasing Th17 over the Treg population. BSP-seq detected that DNA hypermethylation occurred in the Smad7 promoter region of CD4+ T cells obtained from RA patients. Mechanistically, we found that the DNA hypermethylation in the Smad7 promoter of CD4+ T cells was associated with decreased Smad7 expression in RA patients. This was associated with overreactive DNA methyltransferase (DMNT1) and downregulation of the methyl-CpG binding domain proteins (MBD4). Inhibition of DNA methylation by treating CD4+ T cells from RA patients with 5-AzaC significantly increased Smad7 mRNA expression along with the increased MBD4 but reduced DNMT1 expression, which was associated with the rebalance in the Th17/Treg response. Conclusion: DNA hypermethylation at the Smad7 promoter regions may cause a loss of Smad7 in CD4+ T cells of RA patients, which may contribute to the RA activities by disrupting the Th17/Treg balance.